1995
DOI: 10.1021/ma00130a011
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Effects and Form Birefringence in Diblock Copolymers

Abstract: We investigate effects of the electric field on diblock copolymers by assuming an induced dipolar interaction among the composition fluctuations. First, we show that, when an electric field is applied perpendicularly to lamellae, undulations start to grow if their in-plane wavenumbers are smaller than an electric wavenumber qe proportional to the field. Subsequently, the undulations grow into larger spatial structures, eventually leading to a final square-lattice pattern. Second, we calculate the Maxwell stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
115
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 15 publications
5
115
1
Order By: Relevance
“…3,4 It has been shown that by changing temperature [7][8][9] or by applying external fields such as shear flow [10][11][12][13][14][15] or electric fields [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] phase transitions between different ordered structures can be induced. Electric fields have been shown as an effective method of controlling the orientation of the structures.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 It has been shown that by changing temperature [7][8][9] or by applying external fields such as shear flow [10][11][12][13][14][15] or electric fields [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] phase transitions between different ordered structures can be induced. Electric fields have been shown as an effective method of controlling the orientation of the structures.…”
Section: Introductionmentioning
confidence: 99%
“…To do so, let us quickly note the derivation of relaxation terms in Eqs. (10) and (11) due to the interfacial tension [2]. Generally speaking, the effects of the interfacial tension are (i) to reduce the interfacial area and (ii) to make the system isotropic.…”
Section: B Effect Of Electric Fieldmentioning
confidence: 99%
“…Throughout the present paper, we shall assume the above condition to hold but, as a new element, allow the two fluids to have a mismatch in their dielectric constants, which are denoted as 1 =¯ + δ and 2 =¯ − δ . Then the system acquires an ability to respond to an electric field, leading to the shape change of droplets and interfacial instabilities [3][4][5][6][7][8][9][10][11][12]. This change in the domain structure is expected to affect the flow properties of the system, thus giving rise to the electrorheological effect [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, the general relation between the derivatives of the thermodynamic potential and the correlation function of the order parameter, given by Eq. (6), requires the inclusion of the electric field into the correlation function of the Brazovskii self-consistent Hartree approach, too. The angular dependence of the structure factor without taking into account the fluctuation effects was derived previously for polymer solutions in [1], and for copolymer melts in [6].…”
Section: Introductionmentioning
confidence: 99%
“…(6), requires the inclusion of the electric field into the correlation function of the Brazovskii self-consistent Hartree approach, too. The angular dependence of the structure factor without taking into account the fluctuation effects was derived previously for polymer solutions in [1], and for copolymer melts in [6]. Intuitively it seems obvious that fluctuations become anisotropic in an electric field, and moreover fluctuations of modes with wave vectors parallel to the electric field are suppressed.…”
Section: Introductionmentioning
confidence: 99%